A COMPARISON OF RAPID DIAGNOSTIC TESTING (BY PLASMODIUM LACTATE DEHYDROGENASE), AND QUANTITATIVE BUFFY COAT TECHNIQUE IN MALARIA DIAGNOSIS IN CHILDREN - Ifeorah, Ifeanyi Kanayo; Brown, Biobele J; Sodeinde, Olugbemiro O (African Journal of Infectious Diseases (AJID), 2017)
Background: The World Health Organization (WHO) considers early and rapid diagnosis as one of the strategies to control malaria. This study compared the performance of Quantitative Buffy Coat (QBC) test and the Plasmodium lactate dehydrogenase (pLDH) rapid diagnostic test (RDT) with microscopy as the gold standard. Materials and Methods: The study involved children ages 0-5 years who presented with a history of fever at the University College Hospital, Ibadan, Nigeria. Blood was collected from each patient and used for RDT, QBC and Giemsastained blood films for malaria parasites (MP). Results of QBC and RDT were compared with microscopy results for the diagnosis of malaria. Results: A total of 370 cases (194 boys and 176 girls) were studied giving a male: female ratio of 1.1:1. Of the 370 cases tested using Giemsa-stained thick blood films for MP, 78 (21 %) were positive. For the QBC test, 78 (21%) of the cases were positive with sensitivity, specificity, positive and negative predictive values of 70.5 %, 92.1%, 70.5 % and 92.1 % respectively. Seventy-six (20%) of the cases were positive by RDT with sensitivity, specificity, positive and negative predictive values of 84.2 %, 95.2 %, 82.1 %, and 95.9 % respectively. There was no significant difference in the sensitivity of QBC compared with the RDT. Conclusion: Both the QBC and the pfLDH (RDT) performed reasonably well in this study Malaria rapid diagnostic tests are recommended in malaria endemic clinical settings to avoid unnecessary antimalarial treatment.